ANALISIS PENENTUAN PERSEDIAAN BAHAN BAKU KEDELAI DENGAN MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY PADA HOME INDUSTRI TAHU BU IGUK DI WONOGIRI - Dewi Lintang Woroyati; Sunarso Sunarso; Sumaryanto Sumaryanto (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2020)
The purpose of this study was to determine the planning of the supply of soybean raw materials in the Home Industry Tahu Bu Iguk in Wonogiri by used the EOQ (Economic Order Quantity) method in making an economical order. This type of research is a case study. Data collection techniques used interviews, observation and documentation. Data analysis techniques used EOQ analysis. The results showed that the optimal ordering results using the EOQ method per month was 4,665 kg, this case was more economical compared to the average home industry raw material ordering of 4.743 kg. The frequency of purchasing soybean raw materials is 12.20 times, this is more efficient when compared to the company, which is 38 times. The safety stock results for 2019 amounted to 1.158 kg. Reorder point results of 1.523,37 kg per day to be produced into tofu. The results of the calculation of the total cost of raw materials inventory of the Home Industry Tofu Bu Iguk Wonogiri in 2019 with the EOQ method is Rp 1.376.167,80.